Metabolomic insights into plant-derived cyclolinopeptides as natural therapeutics for management of paroxysmal hypertension: an in-silico approach - Mishra, Akanksha; Shrivastava, Rahul; Khare, Ruchi (International Journal Of Community Medicine And Public Health, 2024)
Paroxysmal hypertension is a type of response exerted by the body towards external stimulus like physical, mental, or emotional stress which leads to chemical changes in the body that accelerates the physiological parameters like stress hyper-glycemia, obesity, stress cardiomyopathy, hemorrhagic stroke etc. Due to ill effects of chemical drugs administered by the clinicians, there is need of natural anti-depressant products which may serve as an alternative medicine. Compounds like cyclolinopeptides, cyclosporin A, and curcacyclines have exhibited potential immunosuppressive activity. With objective of drug discovery, this study investigates the role of sub-types of cyclolinopeptides as potential drugs against paroxysmal hypertension and predict their mode of action in biochemical pathways and their role in mitigation of stress induced hyper response.